STUDI POTENSI AIR BAKU DAN RANCANGAN PEMANFAATAN UNTUK KEBUTUHAN DOMESTIK DI PULAU TARAKAN - Kiki Frida Sulistyani; Ery Suhartanto (Universitas Tribhuwana Tunggadewi, 2010)
In this time in Tarakan Island availability of ill assorted water with amount of water required for society. most indicator are water of PDAM emptying into society not fluent and very society him of rainwater. Island of Tarakan have mean rainfall 4000 mm/year and 230 rain day/year. From this study result is got availability of water in Tarakan is 58.351 million m3, while the requirement of until year 2033 is equal to 37.179 million m3, so that the water balance of still surplus that is 21.172 million m3. Result of calculation of balance irrigate in every district, District of North Tarakan 17.32 million m3. District of West Tarakan -9.22 million m3, by 12 deficit month. District of Central Tarakan deficit volume -0.02 million m3 by 1 deficit month and District of East Tarakan -0.15 million m3 by 1 deficit month. District of West Tarakan need water accomodation to fulfill amount of water required, because have do not enable is again woke up by accomodation, hence the water supply of isn't it from District of North Tarakan. While for the District of Central Tarakan and East Tarakan, can isn't it from the region of each. From result of analysis potency location with AHP to get location priority scale to be woke up. Is so that obtained by plan accomplishment of amount of water required in Tarakan up to year 2033, with development 4 of dam in North Tarakan, 1 of dam in Central Tarakan and 1 of dam in East Tarakan